Microbial Exopolysaccharides: Natural Modulators of Dairy Products - Pallavi Jaiswal, Rohit Sharma, Bhagwan Singh Sanodiya, Prakash Singh Bisen (Journal of Applied Pharmaceutical Science, 2014)
Microbial exopolysaccharides (EPS) are considered as natural bio-thickeners abundantly used in dairy and fermented food industries for quality improvement. In fermentation based dairy industries, researchers are seeking their attention on substitution of artificial food stabilizers with naturals by exploring EPS, especially for improving the rheology of fermented food products. Lactic acid bacteria (LAB) being a starter player for fermented food products are believed to be as one of the best natural producers of EPS. These EPS are basically sugar residues, secreted by microbes in their surrounding environment but their in-vitro production is not economical due to the media and processing costs involved. The process of production is also complex due to the involvement of various enzymes and regulatory proteins. With modernization in dairy sector, our understanding towards EPS needs improvement. The review focuses on a brief explanation on the behavior and functionality of EPS from lactic acid bacteria.
Keywords: Exopolysaccharides, Lactic acid Bacteria, Rheology, Fermentation, Starter culture.